Assessment of digital competencies in higher education faculty: a multimodal approach within the framework of artificial intelligence - Moreira-Choez, Jenniffer Sobeida; Gómez Barzola, Ketty Elizabeth; Lamus de Rodríguez, Tibisay Milene; Sabando-García, Angel Ramón; Cruz Mendoza, Juan Carlos; Cedeño Barcia, Lizandro Agustín (Frontiers in Education, 2024)
Introduction Digital competencies are increasingly recognized as a fundamental pillar in the professional development of educators, particularly in Higher Education, where the integration of educational technologies is crucial for enhancing teaching and learning processes. Methods This study assessed the digital competencies of faculty at the Technical University of Manabí using a descriptive, non-experimental approach with a sample of 279 professors. Data collection was conducted through a quantitative multimodal design utilizing the Higher Education Digital Competencies Assessment Questionnaire (CDES). The data were analyzed using a structural equation model in AMOS software. Results The findings revealed a significant correlation between faculty members' perceptions and the evaluated dimensions. However, the analysis identified discrepancies in the goodness-of-fit indices, suggesting the need for adjustments in the model. Discussion The study underscores the importance of ongoing evaluation and optimization of the structural model to refine the integration of digital competencies. It demonstrates the potential of these competencies to enrich teaching practices and concludes that continuous validation and adjustment of the model are essential to align faculty perceptions with their actual digital competencies.